Rekonstruksi dan Reaktualisasi Literasi Ekologi Sosial Islam - Heru Kurniawan (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2016)
Literacy on Islamic social ecology refers to human interaction with the natural environment, technology, and society based on the fundamental principles of Islam.The reconstruction of Islamic social ecological literacy is grounded in the basic tenet of Islam that affirms the human position as a “leader” entrusted with a “mandate” to manage the Earth, including the natural environment and natural resources, in the best possible way.This reconstructed ecological literacy must then be actualized in society.The process of actualization takes the form of concrete activities aimed at instilling awareness of Islamic social ecology within social spaces such as families, communities, and schools. These efforts are organized and supported by the state through policies and regulations.Through the processes of reconstruction and actualization, the state plays an active role in building Islamic social-ecological awareness. This is intended to establish a foundation of awareness, knowledge, and values of Islamic social ecology within society.